2013
DOI: 10.2298/pif1302077k
|View full text |Cite
|
Sign up to set email alerts
|

Diatomaceous earths: Natural insecticides

Abstract: SUMMARYThe regulatory issues for diatomaceous earth (DE) cover three fields: consumer safety, worker safety, and proof of efficacy against pests. For consumer safety, regulatory issues are similar to those for other additives, and a principal benefit of DEs is their removal by normal processing methods. For worker safety, regulatory issues are similar to those for other dusts, such as lime. The proof of potential insecticide values of DE may be assessed by using the analysis of physical and chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
225
2
30

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(266 citation statements)
references
References 45 publications
9
225
2
30
Order By: Relevance
“…Talc was tested as a dust carrier for virus OBs, but we observed that the talc itself strongly affected larval mortality of potato tuberworm due to its fast desiccation effect against newly hatched larvae, as previously described elsewhere (Alcázar et al 1992b, Arthurs et al 2008. Some dry powder carriers have been used as an alternative to synthetic insecticides and are thought to act by imposing mechanical disruption (e.g., mouth parts injuries on chewing insects such as beetles and caterpillars) and physiological stress by absorbing wax from the insect cuticle resulting in water loss (Ebeling 1971, Korunic 1998). Our results demonstrated that talc mixed with low or medium concentrations of the granulosis virus for dusting tubers provides better effectiveness than aqueous virus suspension treatment against potato tuberworm.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Talc was tested as a dust carrier for virus OBs, but we observed that the talc itself strongly affected larval mortality of potato tuberworm due to its fast desiccation effect against newly hatched larvae, as previously described elsewhere (Alcázar et al 1992b, Arthurs et al 2008. Some dry powder carriers have been used as an alternative to synthetic insecticides and are thought to act by imposing mechanical disruption (e.g., mouth parts injuries on chewing insects such as beetles and caterpillars) and physiological stress by absorbing wax from the insect cuticle resulting in water loss (Ebeling 1971, Korunic 1998). Our results demonstrated that talc mixed with low or medium concentrations of the granulosis virus for dusting tubers provides better effectiveness than aqueous virus suspension treatment against potato tuberworm.…”
Section: Discussionsupporting
confidence: 76%
“…Talc dust (magnesium silicate), a dry inert carrier, can be formulated with a virus in a dustable or wettable powder and increase its effectiveness. Besides, it is cheap, easy to obtain, provides UV protection, and can have negative effects on insect behavior and physiology (Helson 1942, Korunic 1998. A dry powder formulation of granulosis virus containing occlusion bodies (OBs) incorporated into talc has been successfully developed and marketed by the International Potato Center in Lima, Peru, as a nontoxic method to protect tubers in nonrefrigerated storage facilities (Lagnaoui et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…DE's adsorptive capacity for lipids, and its insecticidal efficacy, is also affected by the size, shape and a surface topography of diatom species, uniformity of particles and the purity of the formulation (Korunić, 1998(Korunić, , 2013. Depending on the species, size and shape of the diatoms, there are numerous pores and holes in the surface of the diatom particles that make up its active surface.…”
Section: Z Korunić Et Al: a Review Of Natural Insecticides Based Onmentioning
confidence: 99%
“…Particles that have a larger available active surface have a higher sorption capacity for the lipids and are more effective desiccants. Particles of high purity with empty holes being as dry as possible (natural DE after processing usually contain about 4-8% of free water, although 5% is preferable) have the highest sorption capacity and the highest efficacy against insects (Quarles, 1992;Subramanyam and Roesli, 2000;Korunić, 2013).…”
Section: Z Korunić Et Al: a Review Of Natural Insecticides Based Onmentioning
confidence: 99%
“…The manipulation of grain temperature and the use of inert dusts such as diatomaceous earth are examples of promising nonchemical methods for the integrated management of insect pests of stored products (Flinn, 1998;Flinn & Hagstrum, 2002). Diatomaceous earth is derived from sediment diatomaceous alga shell, and when in contact with the insects causes the removal of the wax layer of the cuticle, causing its death by desiccation (Korunic, 1998).…”
Section: Introductionmentioning
confidence: 99%